2013
DOI: 10.1038/nature12341
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Martian meteorite age conundrum using micro-baddeleyite and launch-generated zircon

Abstract: Invaluable records of planetary dynamics and evolution can be recovered from the geochemical systematics of single meteorites. However, the interpreted ages of the ejected igneous crust of Mars differ by up to four billion years, a conundrum due in part to the difficulty of using geochemistry alone to distinguish between the ages of formation and the ages of the impact events that launched debris towards Earth. Here we solve the conundrum by combining in situ electron-beam nanostructural analyses and U-Pb (ura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 28 publications
9
94
0
1
Order By: Relevance
“…This zircon was interpreted as forming as a result of reaction between baddeleyite and high-Si fluid or melt generated during the impact that launched this meteorite into the space. The 206 Pb/ 238 U ages of baddeleyite grains investigated in this study spread between 227 AE 18 and 22 AE 2 Ma, giving both time of baddeleyite crystallization, estimated as 187 AE 33 Ma on the basis of the least disturbed grains, and an upper limit for the impact event given by the youngest baddeleyite analysis (Moser et al 2013). Consequently, published results of U-Pb baddeleyite dating appear to support the young age of basaltic shergottites.…”
Section: U-pb Ages Of Martian Samplessupporting
confidence: 59%
See 1 more Smart Citation
“…This zircon was interpreted as forming as a result of reaction between baddeleyite and high-Si fluid or melt generated during the impact that launched this meteorite into the space. The 206 Pb/ 238 U ages of baddeleyite grains investigated in this study spread between 227 AE 18 and 22 AE 2 Ma, giving both time of baddeleyite crystallization, estimated as 187 AE 33 Ma on the basis of the least disturbed grains, and an upper limit for the impact event given by the youngest baddeleyite analysis (Moser et al 2013). Consequently, published results of U-Pb baddeleyite dating appear to support the young age of basaltic shergottites.…”
Section: U-pb Ages Of Martian Samplessupporting
confidence: 59%
“…Zhou et al (2013) reported 206 Pb/ 238 U age of 182.7 AE 6.9 Ma for baddeleyite from the Zagami meteorite, while Moser et al (2013) investigated baddeleyite crystals overgrown by the submicron zircon grains from meteorite NWA5298. This zircon was interpreted as forming as a result of reaction between baddeleyite and high-Si fluid or melt generated during the impact that launched this meteorite into the space.…”
Section: U-pb Ages Of Martian Samplesmentioning
confidence: 98%
“…Detrital shocked zircons may, moreover, serve as geochronologic tracers for the sedimentary evolution of impact structures on Earth and associated reworking processes (e.g., Cavosie et al, 2010;Moser et al, 2011;Lugo Centeno and Cavosie, 2014;Thomson et al, 2014). In addition to the terrestrial impact cratering record, zircon has been a useful tool in lunar (Zhang et al, 2011;Grange et al, 2013) and Martian (e.g., Moser et al, 2013) impact geochronology.…”
Section: Use Of Zircon In Impact Crater Datingmentioning
confidence: 98%
“…Metamorphic precipitation of zircon could be a result of the breakdown of and/or exsolution from various Zr-bearing phases (Davidson and van Breemen, 1988) such as garnet, amphibole, (clino)pyroxene and ilmenite (e.g., Fraser et al, 1997;Degeling et al, 2001;Möller et al, 2003;Söderlund et al, 2004;Harley et al, 2007;Kelsey et al, 2008;Morisset and Scoates, 2008), hemo-ilmenite (Morisset et al, 2005), baddeleyite (Bingen et al, 2001;Söderlund et al, 2004), rutile (Harley et al, 2007;Tomkins et al, 2007;Morisset and Scoates, 2008;Kelsey and Powell, 2011;Ewing et al, 2013Ewing et al, , 2014Pape et al, 2016), epidote, titanite (Kohn et al, 2015), chlorite (Fraser et al, 2004), and biotite (Vavra et al, 1996). Zircon coronae have been reported around Martian baddeleyite as a result of shock metamorphism (Moser et al, 2013). In mafic metamorphic rocks, precipitation of zircon is commonly associated with the Fe-Ti oxides (Bingen et al, 2001;Ewing et al, 2013Ewing et al, , 2014 due to similar chemical properties of Zr and Ti.…”
Section: Zr-bearing Phases Potentially Associated With Zircon Precipimentioning
confidence: 99%